2013
DOI: 10.4018/ijcbpl.2013070106
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phones in Data Collection

Abstract: Mobile phones are increasingly popular tools not only for daily use but also for research purposes. The authors systematically searched related literature using mobile phones as a tool for data collection and found 171 publications consisting of review, empirical, methodological, and theoretical studies in various disciplines such as medicine, engineering, and education. After reviewing contributions of previous review studies, the authors presented a description of data collection process consisting of four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 162 publications
0
14
0
Order By: Relevance
“…Our experience using the GOIS app adds to the existing research showing the utility of apps for research data collection on topics as diverse as medicine, engineering, education, time usage studies, and alcohol consumption, 22,23,29 suggesting that smartphone apps can also be useful for research data collection on illicit drug use and drugs policing. Given the challenges in getting access to data on such topics, this is welcome news.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our experience using the GOIS app adds to the existing research showing the utility of apps for research data collection on topics as diverse as medicine, engineering, education, time usage studies, and alcohol consumption, 22,23,29 suggesting that smartphone apps can also be useful for research data collection on illicit drug use and drugs policing. Given the challenges in getting access to data on such topics, this is welcome news.…”
Section: Discussionmentioning
confidence: 96%
“…Overall, such experiences suggest that apps can offer benefits for research data collection. [21][22][23][24]29 Two key challenges in the use of smartphone apps are technical hitches/problems in poor design and privacy: namely that the use of mobile technology makes it harder to control where and how collected data are shared. 21,29,31 That said, increasing studies have showed that piloting and anonymisation can lessen both issues.…”
Section: The Rise Of the Smartphone App Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many works that have considered behavior recognition in ubiquitous computing and their relevant subsets, which focus primarily on pervasive datasets stored in BTSs as a subject of these research interests. Mobile phone datasets have gained both in importance and popularity (see the review paper byŞahin and Zhen [1]), both for empirical and theoretical research purposes concerning medicine [2,3], engineering, education, and even ethnic segregation [4]. The CDR datasets are the subject of intensive pre-handling and cleaning to obtain big dataset for further studies that are concerned with behaviors and activities [5].…”
Section: Related Workmentioning
confidence: 99%